Basic drawing line, light, shade, and texture. ([S.L.] Education Dimensions, 1989)
Produced by Double Diamond Corp., for RH Media Inc. Helps you teach good drawing practice quickly and easily
Pt.1. Drawing with line - pt.2. Light, shade and texture.
VHS format.
Keywords: Drawing -- Technique